Tafsir Bi Al-Ra’y Method and Its Implications for Qur’anic Interpretation in the Modern Era - Faiq Falahi; Miftah Ulya; Amin Zaki (Yayasan Adra Karima Hubbi, 2024)
The Tafsir Bi Al-Ra’y method, meaning interpretation of the Qur’an based on independent reasoning, has been a key approach in Qur’anic exegesis since the early days of Islamic thought. Scholars have debated its legitimacy, given its reliance on the interpreter’s reasoning. In the modern era, with new social, political, and scientific developments, Tafsir Bi Al-Ra’y has gained renewed relevance. This study examines how modern exegetes use this method to address contemporary issues while maintaining fidelity to Islamic teachings. It also evaluates the strengths and limitations of Tafsir Bi Al-Ra’y in providing relevant guidance in today’s context. The research employs a qualitative approach, comparing classical interpretations by scholars like Al-Razi and Al-Ghazali with modern figures such as Muhammad Abduh and Sayyid Qutb. Thematic analysis reveals that Tafsir Bi Al-Ra’y offers flexibility in addressing issues such as gender equality, scientific advancements, and social justice. Modern interpreters use this method to make the Qur’an’s message more relevant to contemporary society while preserving its core values. The study concludes that Tafsir Bi Al-Ra’y is a valuable tool for contemporary Qur’anic interpretation, bridging the gap between traditional Islamic teachings and modern realities, making the Qur’an more accessible to present-day challenges.